Sastra, Perempuan, dan Istana Dalam Kronik Melayu Sulalatus Salatin - Rizqi Handayani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This article aims to examine the gender roles and functions played by palaceladies in Malay chronicles, from solely domestic functions to public functions where women can play a diplomatic role through marriage institutions. This research is a qualitative research based on literature sources. Through the Sulalatus Salatin script rewritten by A. Samad as primary data, as well as articles, books and other Malay saga as secondary data, this study found that palace ladieswere still confronted with domestic roles surrounding marriage. However, the marriage that took place in the Malay palace involved women in decision making. This shows the form of independence carried out by palace ladies in a diplomatic marriage. The passivity that is still displayed by some other female figures in the Malay narrative is the strengthening and preservation of patriarchal ideology through discourses of power that arise through political institutions and socio-cultural practices. Thus, it can be concluded that in Sulalatus Salatin there has been an author's effort to reconstruct the role of women in the domestic and public sphere although not yet in a large portion.This is shown by the marriage of the palace which became a political commodity for the interests of men.Marriage and reproductive functions in the palace tend to be political, namely to continue and strengthen the royal bloodline and throne.Artikel ini bertujuan untuk melihat peran dan fungsi gender yang dimainkan oleh para perempuan istana dalam kronik Melayu, dari semata-mata fungsi domestik menuju fungsi publik di mana perempuan dapat memainkan peran diplomatis melalui institusi perkawinan.Penelitian ini merupakan penelitian kualitatif yang berbasis pada sumber-sumber kepustakaan.Melalui naskah Sulalatus Salatin yang diselenggarakan oleh A. Samad sebagai data primer, serta artikel, buku, dan hikayat-hikayat Melayu lainnya sebagai data sekunder maka penelitian ini menemukan bahwa perempuan-perempuan istana masih dihadapkan pada peran-peran domestik seputar perkawinan. Namun, perkawinan yang terjadi dalam istana Melayu melibatkan perempuan dalam pengambilan keputusan.Hal ini menunjukkan bentuk kemandirian yang dilakukan para perempuan istana dalam sebuah perkawinan diplomasi.Adapun kepasifan yang masih dipertunjukkan oleh sebagian tokoh perempuan lainnya dalam narasi Melayu merupakan pengokohan dan pelestarian ideologi patriarkis melalui wacana-wacana kekuasaan yang muncul melalui institusi politik dan praktik-praktik sosial-budaya. Dengan demikian, dapat disimpulkan bahwa dalam Sulalatus Salatin sudah ada upaya pengarang untuk merekontruksi peran perempuan dalam ranah domestik dan publik dengan memberikan citra kemandirian, meskipun belum dalam porsi yang luas..Hal ini ditunjukkan dengan perkawinanistana yang menjadi komoditas politik bagi kepentingan laki-laki.Perkawinan dan fungsi reproduksi dalam istana cenderung bersifat politis yaitu untuk meneruskan dan mengokohkan garis keturunan dan tahta kerajaan. يهدف هذا البحث إلى النظر في الأدوار الجنسانية والوظائف التي تلعبها نساء القصر في تاريخ الملايو، من الوظائف المنزلية فقط إلى الوظائف العامة حيث يمكن للمرأة أن تلعب دورًا دبلوماسيًا من خلال مؤسسات الزواج. هذا البحث هو بحث نوعي يعتمد على المصادر الأدبية